MERGER SEBAGAI UPAYA PENGEMBANGAN PERUSAHAAN - Sri Retno Widyorini (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
The policy of deregulation and simplifying bureaucracy with the purpose of encouraging the development of business world receives a warm welcome from the national private entrepreneurs. The above-mentioned deregulation and simplifying bureaucracy refer to investments, both domestic investments and foreign investments, also development through merger, consolidation, and acquisition. Merger, as one of many company development efforts, is regulated inAct no. 40 year 2007 concerning limited company, which is a concrete form of economic legal system renewal in Indonesia. Merger is an effort of company rescue through a unification of one or more companies by maintaining the existence of one company and liquidating the other company (ies). Business actor prefer merger more to other methods as the effort of developing the company